Bhinneka Tunggal Ika: Real Proof Of The Power Of Pancasila - Yuniarto, Bambang; Nisa, Dita Aulia; Setianingsih, Nur Aisyah Addiessuci; Illah, Ahmad Ridho; Ilham, Muhamad (International Journal Labs, 2024)
Indonesia is a nation rich in diversity, encompassing a variety of ethnic groups, religions, languages, and cultures. The concept of Bhinneka Tunggal Ika—